SEG Technical Program Expanded Abstracts 2009 2009
DOI: 10.1190/1.3255284
|View full text |Cite
|
Sign up to set email alerts
|

Local frequency as a direct hydrocarbon indicator

Abstract: L Lo oc ca al l f fr re eq qu ue en nc cy y a as s a a d di ir re ec ct t h hy yd dr ro oc ca ar rb bo on n i in nd di ic ca at to or r L Lo oc ca al l f fr re eq qu ue en nc cy y a as s a a d di ir re ec ct t h hy yd dr ro oc ca ar rb bo on n i in nd di ic ca at to or r S Sh he en ng gh ho on ng g T Ta ai i, , C Ch ha ar rl le es s P Pu ur ry ye ea ar r, , J Jo oh hn n P P. . C Ca as st ta ag gn na a, , U Un ni iv ve er rs si it ty y o of f H Ho ou us st to on n. . SummaryAs a seismic wave propagates, it lose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…4b, suggest that some stations exhibit elevated V/H-amplitudes around 2 Hz. It was suggested that these or similar features could carry information on reservoir-related modifications in the wave-field (Dangel et al, 2003;Lambert et al, 2009;Saenger et al, 2009;van Mastrigt and Al-Dulaijan, 2008). Four spectral seismic attributes are used in this study to quantitatively describe these features and to map their distribution in space and time.…”
Section: Features Of Interestmentioning
confidence: 98%
See 2 more Smart Citations
“…4b, suggest that some stations exhibit elevated V/H-amplitudes around 2 Hz. It was suggested that these or similar features could carry information on reservoir-related modifications in the wave-field (Dangel et al, 2003;Lambert et al, 2009;Saenger et al, 2009;van Mastrigt and Al-Dulaijan, 2008). Four spectral seismic attributes are used in this study to quantitatively describe these features and to map their distribution in space and time.…”
Section: Features Of Interestmentioning
confidence: 98%
“…Therefore the studies are not able to falsify the hypothesis for these reservoirs. Results from other case-studies are more positive with respect to the hypothesis but unfortunately these studies either (i) offer only limited conclusiveness because of high anthropogenic noise and/or complex geology Saenger et al, 2009;Schechinger et al, 2009), (ii) only provide an incomplete description of the applied processing methods (van Mastrigt and Al-Dulaijan, 2008) or (iii) present only isolated measurements (Dangel et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Tai et al, (2009) described that when a seismic wave travels through the subsurface, the properties of the seismic wave -e.g. amplitude and frequency content -are affected by, among other things, geological structures, layer thicknesses, lithology, maturation of porosity and fluid properties in the reservoir.…”
Section: List Of Tablesmentioning
confidence: 99%
“…It is this information that we try to decipher based on our objectives. Tai et al (2009) consider the phenomenon of low-frequency energy anomalies associated with reservoir zones (Figures 1 and 2). One sees in their analysis that the connection between hydrocarbon occurrence and the character of low-frequency anomalies is not always simple.…”
Section: List Of Tablesmentioning
confidence: 99%